FULL E-BOOK INDONESIAN LAW JOURNAL VOLUME 17 N0. 2, 2024 - Muhammad, Fahrurozi; Widayat, Wisnu; Hartati, Besse; Adillah, Muhammad Arief; Sihombing, Putrida; Rangkuti, Liza Hafidzah Yusuf; Batubara, Dinda Aprilia; Syam, Farhans Mahendra; Chang, Soonpeel; Gonzales, Marcellino (Indonesian Law Journal, 2024)
The 2024's second edition of Indonesian Law Journal Volume 16 has been published. The discussion topic of this edition is Legal Impact of Geopolitical Tensions on International Trade Agreements and Business and Human Rights National Strategy in relation with Business and Investment Policy. This edition presents 6 (six) articles from authors with various backgrounds. Please enjoy reading as we hope these article in our Journal are beneficial and constructive towards the development of national law.